THE EFFECT OF OPHIOCEPHALUS STRIATUS EXTRACT ON SERUM LEPTIN LEVEL OF CANCER CACHEXIA PATIENTS - Rury Armayni Siregar, Andri Mardia & Dairion Gatot (International Journal of Research Science and Management, 2021)
Cancer is a disease caused by the abnormal growth of tissue cells that turn into cancer cells. Cancer can cause severe adverse effects for nutritional status. One of the nutritional problems that need attention in cancer patients is cachexia. The pathophysiology of cancer cahexia is multifactorial and not fully understood. Until now, the inflammation is a common concept raised by several studies on cancer cachexia. Leptin is a hormone produced by adipose tissue and is a member of adipocytokines that play a role in adipose tissue signaling hormones. Leptin plays an important role in signaling that regulates energy homeostasis is both central and peripheral, reduce appetite, adipose tissue mass and body weight. Cork fish or Snakehead (Family Channidae) are known to contain higher protein than other fish species. Cork fish is a potential source of albumin. This study was conducted with the aim to determine the effect of cork fish extract on serum leptin levels in cancer cahexia patients. This study is an open label clinical trial with one group pretest-posttest design. The study was conducted in July - December 2019 at the Haji Adam Malik Hospital in Medan with the approval of the USU FK Research Ethics Commission. Data were analyzed using SPPS program where p <0.05 was considered significant. This study showed that there was a significant difference in the serum leptin levels of the subjects before and after receiving Ophiocephalus striatus extract for two weeks.